2012
DOI: 10.1111/j.1365-2036.2012.05118.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of NSAIDs and Helicobacter pylori to the aetiology of endoscopically‐diagnosed peptic ulcer disease: observations from a tertiary referral hospital in the UK between 2005 and 2010

Abstract: SUMMARY BackgroundRecent data from Western countries indicate that the aetiology of peptic ulcer disease (PUD) is changing as the prevalence of Helicobacter pylori is decreasing while the use of low-dose aspirin (LDA, 325 mg/day) is increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 42 publications
(90 reference statements)
4
31
0
Order By: Relevance
“…Studies from the 1980s and 1990s, showed the prevalence of H. pylori infection was 90% in duodenal ulcer and 70% in the gastric ulcer (10) . The prevalence of H. pylori infection has been decreasing steadily over the last decades, especially in industrialized countries while the prevalence of peptic ulcer associated with the use of NSAID apparently is increasing (9,14,15) . The prevalence of peptic ulcer not related to H. pylori nor NSAID -idiopathic PUD -is increasing according to some studies (4,9,24) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the 1980s and 1990s, showed the prevalence of H. pylori infection was 90% in duodenal ulcer and 70% in the gastric ulcer (10) . The prevalence of H. pylori infection has been decreasing steadily over the last decades, especially in industrialized countries while the prevalence of peptic ulcer associated with the use of NSAID apparently is increasing (9,14,15) . The prevalence of peptic ulcer not related to H. pylori nor NSAID -idiopathic PUD -is increasing according to some studies (4,9,24) .…”
Section: Introductionmentioning
confidence: 99%
“…In North America, it has been reported as 20% to 40%, in Southern Europe as 4.1% to 8% and the Northern Europe as 10% to 15%. Asia and undeveloped countries have low prevalence of idiopathic peptic ulcer (15) . Recent data available from Brazil still point out for high prevalence of H. pylori infection (19,20,25) and there are mismatched reports on duodenal ulcer prevalence (12,21) .…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, the use of NSAIDs is reportedly the most important cause of upper gastrointestinal (GI) injury (Lassen et al 2006;Cai et al 2009;Musumba et al 2012). A similar trend has become apparent in Japan, where the prevalence of drug-induced peptic ulcers should soon surpass that of conventional Helicobacter pylori-infected peptic ulcers (Ootani et al 2006).…”
Section: Introductionmentioning
confidence: 86%
“…This condition can generate bleeding when transforms into erosive gastritis [89], especially in patients with bleeding duodenal or gastric peptic ulcers [90,91] and in patients who chronically consume nonsteroidal anti-inflammatory drugs (NSAIDs), including aspirin, for the purpose of cardioprotection [92][93][94][95]. Other mechanisms invoked to explain iron deficiency in patients infected with H. pylori are related to changes in gastric physiology, particularly changes in gastric pH and the presence of achlorhydria, which significantly reduces the solubility and intestinal absorption of inorganic iron [40].…”
Section: Pathophysiology Of Iron Deficiency By H Pylorimentioning
confidence: 99%